Ethnic employment gaps of graduates in the Netherlands - Paul Bisschop; Bas ter Weel; Jelle Zwetsloot (Tinbergen Institute, 2020)
This research documents ethnic employment gaps for labour-market entrants in the Netherlands in the period 2006-2016. We compare short-term and long-term differences in employment of Dutch graduates with graduates from Moroccan, Turkish, Antillean and Surinamese origin and other (non-)western countries. The analyses focus on graduates from secondary vocational education, which is a group of graduates with many people from ethnic minorities. We document ethnic employment gaps by using an Oaxaca-Blinder decomposition. Our findings suggest that there exist persistent ethnic employment gaps. The gaps are largest for female workers. Part of the ethnic employment gaps are explained by observed characteristics, such as the level of secondary vocational education and the field of study or socioeconomic background and household and neighbourhood characteristics. The substantial unexplained part is present among all ethnic groups and does not disappear over time.
Keywords: J15; J2; J70; 330; Employment; labour-market entry; ethnic minorities